Coexistence of CSF anti-Ma2 antibody and 14-3-3 protein: a diagnostic dilemma between autoimmune encephalitis and Creutzfeldt-Jakob disease, a Case Report - Nianlong Sun; Liangyu Zou; Liangyu Zou; Jian Deng; Jian Deng; Fengqing Wei; Hui Zhang; Hui Zhang (Frontiers in Immunology)
BackgroundAnti-Ma2 antibody encephalitis is a rare paraneoplastic autoimmune encephalitis (AE) caused by anti-Ma2 antibody. Creutzfeldt-Jakob disease (CJD), a group of human prion diseases, is a rapidly advancing and fatal neurodegenerative disorder. The two diseases may display comparable clinical symptoms that are easily misdiagnosed. The 14-3–3 protein in the Cerebrospinal fluid (CSF) is considered a valuable marker for diagnosing CJD. In this report, we discussed a case of anti-Ma2 antibody encephalitis in which the CSF showed positive results for 14-3–3 protein, a new instance of antibody coexistence.Case presentationA 77-year-old man was hospitalized due to his recent rapid progression of memory loss, mental and behavioral abnormalities, and gait disturbance. Brain CT showed no abnormalities. The detection of antineuronal antibodies in serum and CSF using Western blot revealed positive high titers for anti-Ma2 antibody. Surprisingly, the 14-3–3 protein in CSF was positive. Subsequently, FLAIR magnetic resonance imaging showed abnormal regions with heightened signal intensity in the bilateral mesial temporal lobes, amygdala, and hippocampus. Electroencephalography, real-time quaking-induced conversion in CSF, and prion protein gene in blood were detected to distinguish from CJD, and these findings did not match the diagnosis of CJD. Finally, the patient was treated with intravenous methylprednisolone, intravenous immunoglobulin (IVIG), and rituximab. The patient’s condition was effectively improved.ConclusionsAnti-Ma2 antibody encephalitis is a type of encephalitis associated with autoantibodies targeting intracellular antigens. Previous studies have detected the presence of 14-3–3 protein in some cases of AE associated with antibodies against neuronal surface antigens. This is the first report of concomitant anti-Ma2 antibody and CSF 14-3–3 protein positivity, which is a further extension of previous studies. This case demonstrates that CSF 14-3–3 protein positivity does not preclude AE and may reflect secondary neuronal injury. When both antibodies are present simultaneously, the diagnosis should be made in combination with the patient’s imaging features, prion-specific testing and high titers of antineuronal antibodies to avoid delay in treatable disease.